Swasthya Portal: A Boon for Tribal’s Health in India - Acharya Balkrishna; Garima Yadav; Gunjan Sharma; Neelam Rawat Dabhade; Nidhi Sharma; Deepika Srivastava; Vedpriya Arya (Recent Updates in Disease and Health Research Vol. 7, 2024)
Health is among the most significant markers of the quality of a person’s life. Due to their vulnerability and deprivation, tribal inhabitants face a multitude of difficulties; one of the most important aspects contributing to their vulnerability and deprivation is their health. Tribal health has been the focus of discussion for a very long time. In an attempt to address the health concerns these tribes suffer, the Indian government developed the “SWASTHYA” gateway, which provides a number of paybacks. In this paper, authors have focused on the “SWASTHYA” portal’s data analysis and its benefit for the tribal communities in different states. As a result, there is a pressing need to investigate and assess the impact of NGOs’ initiatives on tribal health. In this sense, the author’s personnel experiences working on tribal health issues during the last few years are being reflected.